Reactive astrocytes and Wnt/β-catenin signaling link nigrostriatal injury to repair in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model of Parkinson’s disease - L’Episcopo, F. (2010)
Emerging evidence points to reactive glia as a pivotal factor in Parkinson’s disease (PD) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned mouse model of basal ganglia injury, but whether astrocytes and microglia activation may exacerbate dopaminergic (DAergic) neuron demise and/or contribute to DAergic repair is presently the subject of much debate. Here, we have correlated the loss and recovery of the nigrostriatal DAergic functionality upon acute MPTP exposure with extensive gene expression analysis at the level of the ventral midbrain (VM) and striata (Str) and found a major upregulation of pro-inflammatory chemokines and wingless-type MMTV integration site1 (Wnt1), a key transcript involved in midbrain DAergic neurodevelopment. Wnt signaling components (including Frizzled-1 [Fzd-1] and β-catenin) were dynamically regulated during MPTP-induced DAergic degeneration and reactive glial activation. Activated astrocytes of the ventral midbrain were identified as candidate source of Wnt1 by in situ hybridization and real-time PCR in vitro. Blocking Wnt/Fzd signaling with Dickkopf-1 (Dkk1) counteracted astrocyte-induced neuroprotection against MPP(+) toxicity in primary mesencephalic astrocyte–neuron cultures, in vitro. Moreover, astroglial-derived factors, including Wnt1, promoted neurogenesis and DAergic neurogenesis from adult midbrain stem/neuroprogenitor cells, in vitro. Conversely, lack of Wnt1 transcription in response to MPTP in middleaged mice and failure of DAergic neurons to recover were reversed by pharmacological activation of Wnt/β-catenin signaling, in vivo, thus suggesting MPTP-reactive astrocytes in situ and Wnt1 as candidate components of neuroprotective/neurorescue pathways in MPTP-induced nigrostriatal DAergic plasticity.